Long memory and fractional integration in high frequency financial time series - Guglielmo Maria Caporale; Luis A. Gil-Alana (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper analyses the long-memory properties of high frequency financial time series. It focuses on temporal aggregation and the influence that this might have on the degree of dependence of the series. Fractional integration or I(d) models are estimated with a variety of specifications for the error term. In brief, we find evidence that a lower degree of integration is associated with lower data frequencies. In particular, when the data are collected every 10 minutes there are several cases with values of d strictly smaller than 1, implying mean-reverting behaviour. This holds for all four series examined, namely Open, High, Low and Last observations for the British pound/US dollar spot exchange rate.
Keywords: C22; 330; High frequency data; long memory; volatility persistence; structural breaks; Finanzmarkt; Zeitreihenanalyse; Volatilität; Strukturbruch; Schätzung; Wechselkurs; US-Dollar; Pfund Sterling; Spotmarkt; Welt